2014
DOI: 10.1038/nn.3764
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic circuit motifs underlying rhythmic gain control, gating and integration

Abstract: Brain circuitry processes information by rapidly and selectively engaging functional neuronal networks. The dynamic formation of networks is often evident in rhythmically synchronized neuronal activity and tightly correlates with perceptual, cognitive and motor performances. But how synchronized neuronal activity contributes to network formation and how it relates to the computation of behaviorally relevant information has remained difficult to discern. Here we structure recent empirical advances that link syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
330
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 327 publications
(351 citation statements)
references
References 120 publications
8
330
1
Order By: Relevance
“…4). In previous studies, 5-to 10-Hz activity fluctuations were shown to organize distinct band-limited gamma-frequency bands categorized as low (∼35-55 Hz), medium (∼50-90 Hz), and high (epsilon; ∼90-140 Hz) bands, each likely originating in separable underlying circuit motifs (8,11,26). The observation that ACC/ PFC circuits theta-synchronized the activation at a low-gammafrequency band is, to our knowledge, unprecedented in LFP recordings in the primate brain.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…4). In previous studies, 5-to 10-Hz activity fluctuations were shown to organize distinct band-limited gamma-frequency bands categorized as low (∼35-55 Hz), medium (∼50-90 Hz), and high (epsilon; ∼90-140 Hz) bands, each likely originating in separable underlying circuit motifs (8,11,26). The observation that ACC/ PFC circuits theta-synchronized the activation at a low-gammafrequency band is, to our knowledge, unprecedented in LFP recordings in the primate brain.…”
Section: Discussionmentioning
confidence: 97%
“…A rich set of predominantly rodent studies have documented such interareal neuronal interactions in the form of a phase-amplitude (P-A) correlations between lowfrequency periodic excitability fluctuation and high-frequency gamma-band activity (7)(8)(9). It is, however, unknown whether there are reliable cross-frequency P-A interactions between those primate ACC/PFC nodes that underlie flexible attention shifts and, if so, whether P-A correlations are reliably linked to the actual successful deployment of attention (10,11). We thus set out to test for and characterize P-A interactions during covert control processes by recording local field potential (LFP) activity in macaque ACC/PFC subfields during attentional stimulus selection.…”
mentioning
confidence: 99%
“…This setup can be seen as an extended implementation of the dynamical network motif of feed-forward inhibition, which is frequently encountered in local cortical, cotico-cortical, and thalamo-cortical cicuits (Womelsdorf et al 2014). The most stripped down version of this motif only has an inhibitory connection onto the excitatory subpopulation and common input driving both excitatory and inhibitory subpopulations.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, we 34 and others 35,36,65 have linked MMN deficits to impaired theta-frequency response, and underlying NMDAR dysfunction in rodent 66,67 and primate 28 models. At the local circuit level, theta rhythms are tied to interactions involving non-PV cells, especially somatostatintype inhibitory interneurons 6,29,68 . The present replication of prior theta-frequency findings thus further supports models of impaired function across interneuron types in schizophrenia 6 .…”
Section: Theta Frequency and Ensemble Activity Within Auditory Regionsmentioning
confidence: 99%
“…In ERSP analysis, electrophysiological activity is divided conventionally into discrete delta (.5-4 Hz), theta (4-7 Hz), alpha (7)(8)(9)(10)(11)(12), beta (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and gamma (>24 Hz) bands, which reflect differential underlying local-circuit processes 20,[27][28][29] . Within these bands, stimulus-related activity is further differentiated into those that reflect alterations in phase reset mechanisms as reflected in intertrial coherence (ITC) vs. those that reflect alterations in single-trial power (e.g.…”
Section: Introductionmentioning
confidence: 99%